PENGGUNAAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK DENGAN MEDIA VISUAL DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA DI KELAS I SDN 1 KUWARASAN - Wahyuni, Tri (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Learning Approach of Realistic Mathematic Education (RME) with Visual Media in Improving Mathematic Learning of the First Grade of SDN 1 Kuwarasan. The objectives of this research are: (1) to describe the application of learning approach of RME e with visual media and (2) improve Mathematic learning. This research is a collaborative Class Action Research (CAR) that was conducted in three cycles. Subject of this research are first grade student of SDN 1 Kuwarasan in academic year of 2014/2015 totalling 23 students. The results show that: (1) the application of learning approach of RME technique with visual media has been carried out through five steps, namely: (a) giving contextual problem, (b) explain contextual problem by visual media; (c) solution of contextual problem with visual media; (d) discuss and compare of solution; (e) drawing conclusion with together and (2) the application of learning approach of RME with visual media can improve Mathematic learning. Keywords: RME, visual media, learning, Mathematic Abstrak: Penggunaan Pendekatan Pendidikan Matematika Realistik dengan Media Visual dalam Peningkatan Pembelajaran Matematika di Kelas I SDN 1 Kuwarasan. Tujuan penelitian ini yaitu: (1) mendeskripsikan penggunaan pendekatan PMR dengan media visual dan (2) meningkatkan pembelajaran Matematika. Penelitian Tindakan Kelas (PTK) kolaboratif yang dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah siswa kelas I SDN 1 Kuwarasan tahun ajaran 2014/2015 yang berjumlah 23 siswa. Hasil penelitian menunjukkan bahwa: (1) penggunaan pendekatan PMR dengan media visual dilaksanakan melalui lima langkah, yaitu: (a) pemberian masalah kontekstual menggunakan media visual; (b) penjelasan masalah kontekstual dengan media visual; (c) penyelesaian masalah kontekstual dengan bantuan media visual; (d) membandingkan dan mendiskusikan jawaban; (e) penyimpulan jawaban secara bersama dan (2) penggunaan pendekatan PMR dengan media visual dapat meningkatkan pembelajaran Matematika. Kata kunci: PMR, media visual, pembelajaran, Matematika